RANCANG BANGUN MESIN PENCACAH UBI MODEL ROTARY UNTUK BAHAN BAKU PAKAN TERNAK KAPASITAS 100 KG/JAM - Tambunan, Ari Perdana; Nurdiana, Nurdiana; Yulfitra, Yulfitra; sutrisno, Franky; Siagian, Tony (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
Cassava is one of the animal feeds, namely poultry and fish feed, etc. Its use is very beneficial for farmers easily to get this material. The processing of cassava is by chopping small cassava by chopping manul. This method is felt to be less efficient for a large amount because it will take a lot of time and energy, so by making the solution with a wake up design. in this design, it is devoted to the calculation of its components. In this design, the power used is 3.519 kw with a 2000 rpm engine speed, turning a 40 mm shaft using a 3 inch pulli 4 inch pulli with a 1500 rpm dish rotation using a V type A belt, with 9 blades in the tube.